Pola Konsumsi Kopi Pada Penderita Hipertensi Di Kecamatan Medan Perjuangan, Kota Medan - citra cahyati nst cahyati nst (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
High levels of caffeine in coffee can make a person's blood pressure increase hypertension 3-4 times because when caffeine enters the flow blood, the hormone adrenaline which makes it difficult to sleep will increase so that blood pressure will also increase. This research is a rapid survey study with univariate analysis, conducted in Medan Perjuangan Subdistrict in November 2019. The sample was 210 people with hypertension with data collection tools in the form of questionnaire instruments. The majority of respondents are women, the most age is 52-59 years, the majority of jobs are housewives. As many as 47 people consume coffee regularly, the average coffee consumption frequency is 1,457 cups/day, with an average size of 198,105ml, an average coffee size of 1,674 tablespoons and an average coffee consumption period of 18,383 years. Systolic blood pressure of respondents who consumed routine coffee most in the category 140-159mmHg (66%) and diastolic blood pressure of respondents who consumed coffee most frequently in the category 90-99mmHg (48.9%). The average coffee consumption of respondents did not exceed the maximum coffee consumption limit for people with hypertension, but it would be better if you do not consume coffee at all.